Association Between White Matter Networks and the Pattern of Striatal Dopamine Depletion in Patients With Parkinson Disease. (13th December 2022) - Chung, Seok Jong; Kim, Yae Ji; Kim, Yun Joong; Lee, Hye Sun; Jeong, Seong Ho; Hong, Ji-Man; Sohn, Young H.; Yun, Mijin; Jeong, Yong; Lee, Phil Hyu
Abstract : Objectives: Individual variability in nigrostriatal dopaminergic denervation is an important factor underlying clinical heterogeneity in Parkinson disease (PD). This study aimed to explore whether the pattern of striatal dopamine depletion was associated with white matter (WM) networks in PD. Methods: A total of 240 newly diagnosed patients with PD who underwent 18 F-FP-CIT PET scans and brain diffusion tensor imaging at initial assessment were enrolled in this study. We measured 18 F-FP-CIT tracer uptake as an indirect marker for striatal dopamine depletion. Factor analysis–derived striatal dopamine loss patterns were estimated in each patient to calculate the composite scores of 4 striatal subregion factors ( caudate, more-affected and less-affected sensorimotor striata, and anterior putamen ) based on the availability of striatal dopamine transporter. The WM structural networks that were correlated with the composite scores of each striatal subregion factor were identified using a network-based statistical analysis. Results: A higher composite score of caudate (i.e., relatively preserved dopaminergic innervation in the caudate) was associated with a strong structural connectivity in a single subnetwork comprising the left caudate and left frontal gyri. Selective dopamine loss in the caudate was associated with strong connectivity in the structural subnetwork whose hub nodes were bilateral thalami and left insula, which were connected to the anterior cingulum. However, no subnetworks were correlated with the composite scores of other striatal subregion factors. The connectivity strength of the network with a positive correlation with the composite score of caudate affected the frontal/executive function either directly or indirectly through the mediation of dopamine depletion in the caudate. Conclusions: Our findings indicate that different patterns of striatal dopamine depletion are closely associated with WM structural alterations, which may contribute to heterogeneous cognitive profiles in individuals with PD.